Clinical efficacy and safety of rimegepant in the treatment of migraine: a meta-analysis of randomized controlled trials - Wang, Qinghui; Wang, Shuangmei; Zhu, Yi; Lin, Fei (Frontiers in Neurology, 2023)
Background This study aims to evaluate the clinical efficacy and safety of rimegepant for the treatment of migraine in adult patients using a meta-analysis. Methods The PubMed, EMBASE, and Cochrane Library were searched up to March 2022. Only randomized controlled trials (RCTs) that evaluated migraine and other comparator treatments in adult patients were included. The clinical response at the post-treatment evaluation, including acute pain free and relief effect, whereas the secondary outcomes were the risk of adverse events (AEs). Results A total of 4 RCTs involving 4,230 patients with episodic migraine were included. Outcome indicators for the number of pain free and relief patients at 2 h, 2–24 h, 2–48 h post-dose showed that rimegepant had better effects relative to the placebo [free at 2 h: OR = 1.84, 95% CI (1.55, 2.18), P < 0.00001; relief at 2 h: OR = 1.80, 95% CI (1.59, 2.04), P < 0.00001]. And there was no significant difference between the occurrence of adverse events in the experimental and control groups [OR = 1.29, 95% CI (0.99, 1.67), P = 0.06]. Conclusion Rimegepant has better therapeutic effects compared to placebo and no significant difference in adverse events.